Problem and Project Based Questions in the Indonesian Language Book for Grade XI Published by Erlangga: Muatan Soal Berbasis Problem dan Project pada Butir Soal Buku Bahasa Indonesia Kelas XI Terbitan Erlangga - Susanto, Rahmad Nanda Viky; Kholis, Hannan Fuad; Adtya, Rizal Friska (RADIANT: Journal of Applied, Social, and Education Studies, 2024)
As a student companion book, textbooks must have content that can encourage students to think at a high level in order to face the development of education in the independent curriculum. This study aims to identify the content of HOTS questions based on problems and projects in the Indonesian Language textbook published by Erlangga in 2022. This study uses a qualitative descriptive approach with content analysis techniques. The data in this study are in the form of problem-based and project-based questions in the book Competent in Indonesian Language for Senior High School/Vocational High School Class XI published by Erlangga in 2022. The data collection technique in this study used document studies. The data validity technique in this study used triangulation of sources and theories. The results of this study show that there are 68% problem-based questions and 32% projects in the Indonesian Language textbook published by Erlangga in 2022. This shows that this book has not been able to balance the composition of problems and projects that support the implementation of the independent curriculum. However, the existence of these HOTS questions is able to support students' high-level thinking skills in the independent curriculum.